Pengaruh Whistleblowing System, Budaya Organisasi dan Moralitas Individu Terhadap Pencegahan Fraud pada PT. Pelabuhan Indonesia III (Persero) Benoa Bali - Candra Restalini Anandya; Desak Nyoman Sri Werastuti (Jurnal Ilmiah Akuntansi dan Humanika, 2020)
This study was conducted to examine the effect of whistleblowing system, organizational culture and individual morality on fraud prevention at PT. Pelabuhan Indonesia III (Persero). Numerical analysis of these variables was used in this study, therefore quantitative approach was applied. The population of this study was 65 employees of PT. Pelabuhan Indonesia III (Persero). The sample of this study was determined by the saturation sampling technique (census) in which the sample chosen was the the entire of population. Data were collected by using a questionnaire with Likert scale. Then the data were analyzed with several analyzes such as data quality tests which included validity and reliability tests, descriptive statistical tests, classic assumption tests which included normality tests, multicollinearity tests, heteroscedasticity tests and autocorrelation tests, and multiple linear regression analysis assisted with SPSS 25 program. The results indicated that the whistleblowing system had a positive and significant effect on fraud prevention, organizational culture had a positive and significant effect on fraud prevention, and individual morality had a positive and significant effect on fraud prevention.